(untitled) (Perner’s Contacts, 2016)
The periodic line transport is an integrated tact timetable, which is also a periodical liner form of surveillance and network interconnection. An important factor is to minimize the interchange times in selected areas - transport hubs. The aim is to minimize the total transit time of a passenger from point A to point B. The cornerstone of transport services is to provide travel opportunities by creating of the links and connections. Often, after the introduction of the new timetable under discussion whether it is better or worse, each approach is evaluated in a subjective manner. The authors solved some partially problematic of rail passenger quality services. At present, there is no methodology for train timetables assessing from the transportation point of view as a whole. We evaluate only specific trains and connections in the stations, but not the quality of the connection from point A to point B. The aim of this paper is to introduce a new methodology for the assessment of timetables in terms of passenger traffic focused on connectivity and linking. From the passenger’s point of view, it is necessary to assess the availability of travelling opportunities between selected points on the rail network. The travel offered from A to B is in principle affected by travel time, number of transfers (changing of the transport means, and number of travel opportunities. Several factors also affect the connectivity and linking. This is an outcome for setting of draft criteria for connection evaluation. Introduced study is designed in purview of the set up a tool for an objective evaluation of the quality of public transport service, specifically, the aspects of availability and time services in selected geographical areas in reciprocity to the Standard EN 13816.